Features of the training process of handball players of higher qualification between rounds in the competitive period - V.A. Tyshchenko (H.S. Skovoroda Kharkov National Pedagogical University, 2015)
Purpose : the technology of preparation of athletes in accordance with the requirements of the system approach. Team management methodology disclosed in terms of the training process in the competitive period between rounds of the regular championship of Ukraine. Material : the experiment involved 85 athletes aged 18-32 years. Results : The recommended during pilot training to perform technical and tactical actions in lockstep future games. Testing and modeling training - at a more complete simulation of conditions of competition. Shock training to perform with significant excess volume and intensity. Shock-modeling training - close to a match where the simulated conditions and confounding factor. The most efficient and effective indicators to consider: the number of substitutions in one match - 8-12 times; residence time player on the court - 12-15 minutes; preferred time of travel players during replacement - 3-5 minutes; heart rate after a rest - 100-120 beats per minute. Conclusions : The developed model microcycle training process handball players between rounds of the Championship of Ukraine.